Incidence of the WTO Anti-Discrimination Rules on Corporation Income Taxation - Hatice Jenkins; Glenn Jenkins (Queen's University, Department of Economics, 2007)
Many countries with free trade zones or export processing zones now exempt from corporate income taxation the income of firms exporting from these areas. The WTO has attempted to eliminate this exemption through its rules to promote the non-discrimination of fiscal systems with respect to export production. In particular, these rules do not allow countries to exempt the income of firms exporting from Free Trade Zones from corporate income taxation. This paper examines both theoretically as well as empirically the incidence of removing this corporate income tax exemption. The empirical analysis is carried out for the case of the Dominican Republic. The findings indicate that in the case of the Dominican Republic the removal of the corporate income tax exemption would inflict a burden on labour equal to about 6 times the amount of additional corporate tax revenue collected from the companies operating in its free trade zones.
Keywords: H22; F13; 330; WTO; tax incidence; Free Trade Zones; corporate taxation; Freihandelszone; Sonderwirtschaftszone; Unternehmensbesteuerung; Steuervergünstigung; WTO-Recht; Dominikanische Republik